Kondisi stres pada karyawan mempengaruhi tingkat konsumsi gula sederhana dan natrium - Cita Eri Ayuningtyas; Nurul Putrie Utami; Widodo Hariyono; Retno Natalina (Jurnal Gizi Klinik Indonesia, 2019)
Stress in work staff influenced simple sugar and sodium intakeBackground: Stress is a condition that occurs to individual experiences a burden of a problem that can not solve there for lead to an unspecific response from the body. One of the causes of stress is the load of work. Stress caused by work could lead to obesity, cardiovascular disease, and diabetes. Change of behavior during stress like eating behavior cause of changing appetite on the individual.Objective: This research was aimed to analyze simple glucose and sodium intake during stress in staff.Method: This was a cross-sectional research design. A total of 125 subjects were chosen by purposive random sampling. The subject was the educational staff of Universitas Ahmad Dahlan. Data was collected as identity, nutrition intake used the Semi-Quantitative Food Frequency Questionnaire (SQFFQ), and stress level used Depression Anxiety Stress Scales (DASS) questionnaire. The statistical test used the Chi-Square test.Results: There is no significant difference between a simple sugar and sodium intake to stress level (p>0.05). The average of simple sugar and sodium intake classified as normal as much as 56.49±77.20 g for simple sugar intake and as much as 653.30±464.55 mg for sodium derived from food ingredients added salt and preservative foods. Data characteristic showed that the nutritional status of 40,8% of the staff was overweight and obese. Conclusions: There is no significant difference between stress level and simple sugar and sodium intake.